Synthesis Organonitrogen Compounds from Patchouli Alcohol Through Ritter Reaction with Acetonitrile and Its Toxicity to Artemia salina Leach. - Khoirun Nisyak; Mohammad Farid Rahman; Sutrisno Sutrisno (Chemistry Department, The University of Brawijaya, 2013)
Patchouli oil contains a compound with biological activities to human body called the patchouli alcohol that can be further developed in medical field. This research aimed to synthesize organonitrogen compound from patchouli alcohol through Ritter reaction with acetonitrile and discover its toxicity towards Artemia salina Leach. The isolation of patchouli alcohol from patchouli oil using fractional distillation under reduced pressure method. The synthesis of organonitrogen compound is done at room temperature with the mol ratio of patchouli alcohol: acetonitrile: sulfuric acid is 1:1,5:4 for 24 hours. The result showed that the amount of patchouli alcohol produced from fractional distillation is 65,25%. The main product yielded from the synthesis between patchouli alcohol and acetonitrile through Ritter reaction is 36,93 % of N-(4,8a,9,9-tetramethyl decahydro-1,6-methanonaphtalene-1-yl) acetamide. Starting material used have LC50 of 77,39 ppm. The product of synthesis have higher toxicity level than starting material, which have LC50 value is 10,39 ppm with the potential as medical compounds.